70-Kilodalton heat shock polypeptides from rainbow trout: characterization of cDNA sequences. - Kothary, R K (1984)
RTG-2 cells, a line of fibroblasts from rainbow trout (Salmo gairdnerii), are induced to synthesize a distinct set of heat-shock polypeptides after exposure to elevated temperature or to low concentrations of sodium arsenite. We isolated and characterized two cDNA sequences, THS70.7 and THS70.14, encoding partial information for two distinct species of 70-kilodalton heat shock polypeptide (hsp70) from these cells. These sequences are identical at 73.3% of the nucleotide positions in their regions of overlap, and their degree of sequence conservation at the polypeptide level is 88.1%. The two derived trout hsp70 polypeptide sequences show extensive homology with derived amino acid sequences for hsp70 polypeptides from Drosophila melanogaster and Saccharomyces cerevisiae. Northern blot analysis of RNA from arsenite-induced RTG-2 cells, with the trout hsp70 cDNAs as probes, revealed the presence of three hsp70 mRNA species. Southern blot analysis of trout testis DNA cleaved with various restriction endonucleases revealed a small number of bands hybridizing to the hsp70 cDNAs, suggesting the existence of a small family of hsp70 genes in this species. Finally, trout hsp70 cDNA sequences cross-hybridized with restriction fragments in genomic DNA from HeLa cells, bovine liver, Caenorhabditis elegans, and D. melanogaster.